(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
REVIEW. Sonia Vaupot. Les enjeux culturels de la traduction. Ljubljana: Univerza v Ljubljani, Filozofska fakulteta, 2015, 245 PP.